INTERNATIONAL LEGAL FRAMEWORK FOR REGULATING LABOR MIGRATION - Khujaeva Shirinkhon (Scholar Express Journals, 2023)
The given paper analyzes the International standards for protecting migrant rights and proposes a system that can effectively protect the rights of migrant workers. The improvement of international instruments in the field of migration is extremely relevant for the entire world community, as countries are faced with migration flows of people with and without documents. There is also a need to adapt the institutional and legal framework governing labor migration to international standards in order to ensure better management of migration processes. The research is conducted on three main methods, i.e. onlinelibrary research and the analysis of national legislation and sources of international law in regulating migrant rights
Keywords: international migration; global standards; core-rights; universal rights